Anurans from the Serra da Bocaina national park and surrounding buffer area, southeastern Brazil - Garey, Michel V. [UNESP]; Provete, Diogo B.; Martins, Itamar A.; Haddad, Célio F. B. [UNESP]; Rossa-Feres, Denise C. [UNESP] (Pensoft Publishers, 2014)
Here, we review the species of anuran amphibian from the Serra da Bocaina National Park and its buffer area, in the Atlantic Forest of southeastern Brazil, comparing the data from a recent survey with museum records. We surveyed adult and larval anurans in ponds, marshes, and streams discontinuously from May 2008 to January 2011. In total, 63 anuran species were previously known to occur at the Park and its surrounding buffer area. In our survey, we recorded 46 species, of which five represented new records, and 22 appeared only in the historical list. Seven topotypic populations were not found in the present study. We suggest that conservation strategies for anurans in the Serra da Bocaina should also consider the surrounding areas that are subjected to anthropogenic pressure, due to the high diversity recorded, high altitudinal variation in species distribution, and various vegetation formations. © 2014 Check List and Authors.